Design and current progress of the Apollon 10 PW project. (2015) - Zou, J.P.; Le Blanc, C.; Papadopoulos, D.N.; Chériaux, G.; Georges, P.; Mennerat, G.; Druon, F.; Lecherbourg, L.; Pellegrina, A.; Ramirez, P.; Giambruno, F.; Fréneaux, A.; et al.
Abstract : The objective of the Apollon project is the generation of 10 PW peak power pulses of 15 fs at 1 shot/minute. In this paper the Apollon facility design, the technological challenges and the current progress of the project will be presented.